Emerson network power : coping with the challenges of a mature technology and increasing competition - Yeung, Jeff Hoi Yan, (SAGE Knowledge. Cases., 2012)
The manufacturing industry in China once won the famous title "World Factory" through providing cheap labor and manufacturing resources. However, the fame and beauty had been fading in recent decades. This case study reveals the key challenges faced by a typical Chinese manufacturer. Increasing threats and pressures could be seen coming from both the supply-side and demand-side. The raw materials supply volatility was leading to a substantial increase in inventory levels to prevent shortages. Meanwhile customers in the global market were continually demanding better customer service, in terms of less stock-out rate and shorter delivery lead-times. Squeezed in the middle of the supply chain, the only feasible way-out for the Chinese manufacturer, Emerson, was to launch effective supply chain initiatives addressing the dual-side pressures. Ultimately the enterprise's cost leadership and competitive position could be enhanced in the global marketplace.